Impairment of Vocal Expression of Negative Emotions in Patients with Alzheimer’s Disease - Han, Kyung-Hun; Zaytseva, Yuliya; Bao, Yan; Pöppel, Ernst; Chung, Sun Yong; Kim, Jong Woo; Kim, Hyun Taek (Frontiers in Aging Neuroscience, 2014)
The vocal expression of emotions (EE) in the retrieval of events from autobiographical memory was investigated in patients in early stages of Alzheimer’s disease (AD). 21 AD patients and 19 controls were interviewed, and EE of the reported memories was rated by 8 independent evaluators. The AD group had lower EE of both recent and remote memory than controls, although EE in remote memories was better preserved in both groups. We observed positive correlations between EE and indicators of cognitive competence in AD patients. AD Patients are impaired in their ability to express emotions at early stages of the disease, and EE seems to deteriorate along with the progression of cognitive impairment.